PENYULUHAN DAN PELATIHAN PEMBUATAN SABUN CUCI PIRING RAMAH LINGKUNGAN BAGI MASYARAKAT DESA TERATAK BULUH - Fadila Sari; Rismaya Leginta Putri; Dhifa Salmadina; Delvi Aprilia; Theresia Natalie; Rizki Fitriadi Romadhani; Rolismen Dike Turnip; Abi Mayu Alamsyah; Has Zazalie Dinda Putra; Natasya Salsabila; Tria Putri Mustika (Bajang Institute, 2023)
This journal aims to examine education and the manufacture of dishwashing soap. Dish washing soap is an ingredient used for all household cooking utensils made from a mixture of alkali (sodium or potassium hydroxide) and triglycerides from C16 carbon chain fatty acids through a saponification reaction. The Real Work Lecture Work Program to Build a Village in Teratak Buluh Village involves housewives in RT 01, RW 01, Dusun I. This Work Program is accompaniment and also teaches housewives in the market village about making laundry soap. plate. It is hoped that this program can be sustainable and have a positive impact on the environment and the welfare of the local community. Hopefully with this soap making training work program, the Teratak Buluh village community can make their own soap products and can open the eyes of the Teratak Buluh village community